The use of modal analysis to examine the lattice structure - Zoltowski, M.; Jeleniewicz, K. (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2019)
Steel structures are subject to large dynamic loads clearly reflected by generated vibration processes. The vibrations may affect state of serviceability of structures by lowering comfort of persons working there as well as possible reaching the level hazardous to safety of the structures. The effect of vibrations to structure is mainly manifested by additional stresses in a given cross-section, which are summed up with those resulting from static loads. The dynamic loads may cause damaging effects in buildings of various structural types or even lead to their destruction. Judging the necessity of improving the quality assessment methods of building structures for purposes of estimation of their state as well as safety factors for lattice structures, the author of this work undertook an attempt to investigate destruction process of selected object by using the modal analysis method.